2020
DOI: 10.3389/fmicb.2019.03159
|View full text |Cite
|
Sign up to set email alerts
|

CusS-CusR Two-Component System Mediates Tigecycline Resistance in Carbapenem-Resistant Klebsiella pneumoniae

Abstract: Background: The increase in carbapenem-resistant Klebsiella pneumoniae (CRKP), especially the emergence of tigecycline-resistant K. pneumoniae (KP), is a serious public health concern. However, the underlying mechanism of tigecycline resistance is unclear. In this study, we evaluated the role of the CusS-CusR two-component system (TCS), which is associated with copper/silver resistance, in tigecycline resistance in CRKP. Methods: Following the in vitro evolution of tigecycline-resistant KP, the minimum inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Meanwhile, the plasmid-mediated high-level TGC resistance gene tetX has recently emerged in animals and humans [10, 17]. Furthermore, the CusS-CusR two-component system is reportedly associated with CRKP resistance to TGC [18]. TGC resistance mechanisms have also been found to be caused by overexpression of tetL and tetM in Enterococcus faecium [19].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the plasmid-mediated high-level TGC resistance gene tetX has recently emerged in animals and humans [10, 17]. Furthermore, the CusS-CusR two-component system is reportedly associated with CRKP resistance to TGC [18]. TGC resistance mechanisms have also been found to be caused by overexpression of tetL and tetM in Enterococcus faecium [19].…”
Section: Introductionmentioning
confidence: 99%
“…Blue-green cyanobacterial mat samples were collected from a small pool at 56 °C with slightly alkaline (pH 8.5–8.9) and sulfidic (46–138 µM) hot spring water [ 18 , 25 , 26 , 27 ] at Nakabusa Hot Springs, Nagano Prefecture, Japan (36°23′33″ N, 137°44′52″ E) [ 20 ]. Microbial mat samples of approximately 3 mm thickness with two distinct vertical layers, a green top layer and an orange-colored bottom layer ( Figure 1 ), were randomly collected in triplicate using a size 4 cork borer (8 mm diameter) as previously described [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction from microbial mat samples was performed as previously described [ 18 ]. Briefly, 0.10–0.21 g wet weight samples were used for RNA extraction with an RNeasy PowerBiofilm Kit (Qiagen, Valencia, CA, USA) following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of such organisms may impede the utilization of silver as antimicrobial agent, especially for medical applications. Furthermore, it has been shown that in some instances, increased metal resistance may be accompanied by an increase in antibiotic resistance ( McHugh et al, 1975 ; Choudhury and Kumar, 1998 ; Perron et al, 2004 ; Dieppois et al, 2012 ; Pal et al, 2017 ; Wang et al, 2017 ; Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%